A descriptive analysis of the paradigm shift from real to reel classroom during Covid-19 Pandemic - Yadav, Anuradha; Yadav, Kavita; Sankhla, Manisha (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
Medical educational institutes have begun offering online classes in preparation for the COVID-19 pandemic. The course work of MBBS phase-I was completed by an online mode of teaching, but the students' satisfaction feedback is still needed to improve online teaching. After receiving approval from the institutional ethical committee, the feedback from 250 Phase-I MBBS students was collected. The student participation was voluntary and 212 students respond about online-classes feedback on the google form. The data were collected and analyzed in Excel and SPSS software. p-value <.05 was considered significant. The majority of students (90 percent of males and 94 percent of females) use their smartphones to attend online classes, and the majority of students experience network problems often or sometimes; only 6% of students were rarely affected by network issues. Only a quarter of students were satisfied with the online mode of teaching, half were neutral and the remaining quarter were unsatisfied. The internet access issue (p-value=0.101) as well as satisfaction level (p-value =0.985) were not affected by the student residence (urban/rural). The majority of students (62%) prefer face-to-face learning in the classroom, whereas 1/4th prefer watching a live playback video of online lectures and only 1/10th choose live-online sessions. Only one-fourth of students were satisfied with online classes and the majority of students suffer from the quality of internet services. Students prefer face-to-face interactive classroom learning. Students acknowledge the benefits of online teaching with the need for further improvement.